Drastic improvement of the trapped field homogeneity in a superconducting hollow bulk by the insertion of a high-Jc superconducting cylinder for NMR bulk magnets. (18th August 2015) - Fujishiro, Hiroyuki; Itoh, Yoshitaka; Yanagi, Yousuke; Nakamura, Takashi
Abstract: Three-dimensional (3D) numerical simulation has been performed for the field-cooled magnetization (FCM) process of REBaCuO superconducting bulk cylinders applicable to the bulk magnet for a 200 MHz (4.7 T) nuclear magnetic resonance (NMR). The influence of the position and size of the defect in the bulk on the inhomogeneity of the trapped field in the hollow space has been investigated. The trapped field profile changes depending on the position and the size of the defect, and the inhomogeneity of the trapped field can be drastically improved by inserting a superconducting thin cylinder with a critical current density ( J c2 ) higher than that of the bulk cylinder ( J c1 ). The superconducting current flows mainly on the outermost surface of the inserted thin cylinder to compensate for the inhomogeneous trapped field caused by the defect. The insertion of the superconducting thin cylinder with a higher J c2 is significantly effective for the practical realization of a compact NMR bulk magnet.